The Intelligentsia in the Civil War: Vikentii Veresaev’s V tupike - David Mandel (RUS (São Paulo))
Vikentiy Veresaev’s novel V tupike (In a Dead-End) was the first major Soviet literary work set in the civil war of 1918-21. It continued Veresaev’s already established literary focus on the evolution of the political and spiritual outlooks among Russia’s socialist intelligentsia, those educated members of society whose life was guided by a commitment to improving the life of the toiling classes. This article focuses on the novel’s depiction of attitudes among the intelligentsia to a central question of the novel: the contradiction between the revolutionary regime’s professed humanistic, socialist goals and the often violent and arbitrary means which it adopted. The article ends with a brief discussion of the novel’s reception, before its ultimate banning in the early 1930s.